Distinctive Competencies and Process of Innovation During Organizationals Merger : The Moderating Effect of Knowledge Vacuum - Ririh, Kirana Rukmayuninda; Anggraeni, Elisa; Machfud, Machfud; Rochman, Nurul Taufiqu (STI Policy and Management Journal, 2023)
Merger organization may encounter contra and supportive conditions. Organizational changes due to merger often occur both process and knowledge intertia. Especially to a research and development agency which its core activity is innovation. Merger among R&D organizations is aimed to achieve legit images but also may delay innovation process. This study measure the effect of knowledge vacuum as a moderating variable between distinctive competencies and process of innovation. 36 targeted researchers and engineers from various former public research & development agencies were involves in a questionnaire survey. Data was analyzed using PLS-SEM. Results show that distinctive competencies significantly affect process of innovation, meanwhile knowledge vacuum is not a significant moderating variable between distinctive competencies and process of innovation. The most important aspects of distinctive competencies are to define detailed process of innovation from start to end and to be able to commercialize innovation output. These aspects will boost changing organization to achieve new goals and maintain innovation process. In this case of insignificant knowledge vacuum, the possibility of open innovation is adequate.